A Study of Nafahāt -e-Tafsīr by Dr. Muhammad Ishaq Qureshi (Al-Qamar, 2025)
Tafsīr holds a central place in Islamic scholarship as the primary means through which the meanings, teachings, and divine guidance of the Qur’ān are understood and conveyed as per someones capacity. It enables readers to grasp the layers of linguistic, moral, legal, and spiritual wisdom embedded in the sacred text, ensuring that its message remains accessible and relevant across generations. The discipline of tafsīr has developed through a rich historical trajectory beginning in the Prophet’s era, expanding through the explanations of the Companions, and maturing into a formalized science through the contributions of early mufassirīn such as al-Ṭabarī, al-Māturīdī, al-Qurṭubī, and others. Over time, diverse methodologies—linguistic, juristic, theological, philosophical, and mystical—shaped the interpretive tradition and enriched its intellectual depth. Within this long continuum, Nafhat e Tafseer by Dr. Muhammad Ishaq Qureshi (d.2021): the tafsīr under study, outlining its scholarly aims, methodological foundations, and unique interpretive features. It explores the author’s approach to Qur’ānic exegesis, sources of reliance, thematic structuring, and contribution to contemporary Qur’ānic studies. By situating this tafsīr within the broader history of interpretation and clarifying its distinctive characteristics, provides readers with a coherent framework to appreciate its value and scholarly significance.
Keywords: Tafsīr, Nafhat e Tafseer, Dr. Muhammad Ishaq Qureshi, Qur’ānic exegesis, Dr. Muhammad Humayun Abbas Shams